KEANEKARAGAMAN SEMUT PREDATOR PERMKUKAAN TANAH (HYMENOPTERA: FORMICIDAE) DI PERKEBUNAN KELAPA SAWIT SPPN SEMBAWA BANYUASIN - Syamsul Rizal; Irham Falahudin; Triya Endarsih (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2011)
ABSTRACTResearch on the diversity of predatory ants (Hymenoptera: Formicidae) of land surface in oil palm plantations SPPN Sembawa Banyuasin conducted in November to December 2010. This research used the temple of traps. Identification results of research conducted at the Laboratory of Biology Department Faculty of Mathematics and Science University of PGRI Palembang and Faculty Tarbiyah State IslamicInstitute Raden Fatah Palembang. The results obtained ant predators comprised 546 individuals from 10 species, 9 genera, and 3 subfamilia. The dominant species in oil palm plantations before harvest is Leptogenys longesis, whereas in oil palm plantations after harvesting is Odoontomachus sp. Predatory ant community diversity index on oil palm plantations before harvest is 2,087, whereas after harvest 1, 372,both growing areas were categorized to have diversity index was. Peradator ant community similarity index on oil palm plantations before mand after harvest by 75%.Key words: diversity, predatory, ants, palm plantations, community similarity